Conclusion: globalisation, inequality, democracy and social cohesion in Asia - Croissant, Aurel (Social cohesion in Asia, 2020)
This chapter discusses the key findings of the individual contributions by examining four topics. First, the comparison of various understandings of social cohesion discussed in this volume suggests that there is no single, universal understanding of this concept in South, Southeast and East Asia. Second, the ‘paradox’ of an inverse relationship between democracy and social cohesion in Asia cannot be explained through the causal channels of globalisation and economic inequality. However, a third argument presented in this chapter is that people’s perceptions of vertical and horizontal inequalities in Asian countries might be a relevant factor for understanding the low trust in political institutions in Asian democracies compared to authoritarian regimes. Fourth, the chapter discusses the ‘dark sides’ of social cohesion, as they manifest itself in various countries especially in South and Southeast Asia. The literature on social cohesion generally views it as something positive, and few studies perceive it as a possible source or conflict. However, the Asian experiences suggest that it is a Janus-faced thing, with potentially both positive and negative consequences for the social, political and economic fabric of societies in the region.
Gesehen am 04.05.2022